Мас-спектрометричні дослідження молекули глюкози - Шпеник, О.Б.; Завілопуло, А.Н.; Агафонова, А.С.; Романова, Л.Г. (Видавничий дім "Академперіодика" НАН України, 2008)
By using a domestic mass-spectrometer MK7304 A, we have studied the yield of ions due to the ionization, including the dissociative one, of molecules of glucose at various temperatures. In the energy region of incident electrons from 5 to 30 eV, we have determined both the energy dependences of the cross-sections of creation of ion-fragments and the thresholds of their creation.